Magnetic and Electrical Properties of Ni3Te2 Single Crystals Grown by Physical Vapor Transport Technique. Issue 7 (30th March 2022) - Jiang, Wan-Yan; Gao, Li-Xin; Fan, Yiwei; Zhao, Gang; Chen, Fei; Cao, Shixun; Li, Zhe; Ge, Jun-Yi
Abstract : High‐quality Ni 3 Te 2 single crystals with length up to 6 mm are successfully grown by the physical vapor transport (PVT) technique. The crystals exhibit unique tubular structures with a hexagonal cross section. The high‐quality crystal is studied by a series of structural and morphological characterization. The physical properties including both magnetization and electrical transport are studied in detail. It is found that there exists a coexistence of weak ferromagnetism and antiferromagnetism at low temperatures. In the measured temperature range of 2–300 K, Ni 3 Te 2 shows a typical metallic behavior, and the temperature dependence of the resistivity ρ x x ( T ) can be well fitted by the parallel‐resistor model. Abstract : Ni3 Te2 single crystals with unique tubular structures and a hexagonal cross section are successfully grown by the physical vapor transport (PVT) technique. Studies of magnetic and electrical transport properties suggest the coexistence of weak ferromagnetism/antiferromagnetism and a typical metallic behavior in Ni3 Te2 .